2009
DOI: 10.1002/nbm.1374
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of multiexponential T2 in rat glioblastoma

Abstract: The aim of this study was to characterize multiexponential T2 (MET2) relaxation in a rat C6 glioblastoma tumor model. To do this, rats (n = 11) were inoculated with the C6 cells via stereotaxic injection into the brain. Ten days later, MET2 measurements were performed in vivo using a single-slice, multi-echo spin-echo sequence at 7.0 T. Tumor signal was biexponential in eight animals with a short-lived T2 component (T2 = 20.7 ± 5.4 ms across samples) representing 6.8 ± 6.2 % of the total signal and a long-live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…The signal intensities of the voxels in the image data will decay exponentially based on the inherent T 2 times, and a T 2 distribution can be created by fitting a sum of exponential decays to the multiple echo decay curve [5]. Multiple echo fitting, using non-negative least squares (NNLS) [5], can be performed to determine the relative proportions of the micro-structural dependent T 2 times [6,7,8,9,10]. In some cases, such as healthy [3,4,11,12] and pathological [13,14,15,10,16] central nervous system tissue, different water environments with separate T 2 times are present within a given voxel, resulting in a decay curve from the voxel being the summation of exponential decays from each constituent T 2 time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The signal intensities of the voxels in the image data will decay exponentially based on the inherent T 2 times, and a T 2 distribution can be created by fitting a sum of exponential decays to the multiple echo decay curve [5]. Multiple echo fitting, using non-negative least squares (NNLS) [5], can be performed to determine the relative proportions of the micro-structural dependent T 2 times [6,7,8,9,10]. In some cases, such as healthy [3,4,11,12] and pathological [13,14,15,10,16] central nervous system tissue, different water environments with separate T 2 times are present within a given voxel, resulting in a decay curve from the voxel being the summation of exponential decays from each constituent T 2 time.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple echo fitting, using non-negative least squares (NNLS) [5], can be performed to determine the relative proportions of the micro-structural dependent T 2 times [6,7,8,9,10]. In some cases, such as healthy [3,4,11,12] and pathological [13,14,15,10,16] central nervous system tissue, different water environments with separate T 2 times are present within a given voxel, resulting in a decay curve from the voxel being the summation of exponential decays from each constituent T 2 time. Four regions are of particular interest: 1) one with a short T 2 time attributed to water trapped between myelin bilayers, called myelin water; 2) one with an intermediate T 2 time attributed to intra-and extracellular water; 3) one with a prolonged T 2 time longer than intra-and extracellular water, which has been noted in pathology [13,14] and in the corticospinal tract of healthy volunteers [13,17]; and 4) one with the longest T 2 time in the distribution, or near that of pure water, that is attributed to cerebrospinal fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Characterizing transverse relaxation with multiple exponentials, or a T 2 spectrum, is of interest in the study of various tissues and samples, including white matter and nerve (1,2), skeletal muscle (3,4), cerebral injury (5), tumor (6), plants (7), food (8), bone marrow (9,10) and more. Such characterization offers the potential to indirectly observe microscopic sample characteristics, such as myelin in white matter; however, it requires a relatively high signal-to-noise ratio (SNR) (1113), so optimization of acquisition and processing methods is important.…”
Section: Introductionmentioning
confidence: 99%
“…33 In a rat glioblastoma model, both short T2 (20.7 AE 5.4 ms) and long T2 (76.4 AE 9.3 ms) were observed in tumor ROIs, whereas a single T2 component (48.8 AE 2.3 ms) was observed for normal GM. 23 In the latter study, the ROI-based approaches used resulted in coarser spatial resolution and reduced detail in T2 histograms. In contrast, our voxel-based analysis method has shown that the T2 times between 30 and 150 ms are related to cellular density and the integrity of the extracellular matrix.…”
Section: Discussionmentioning
confidence: 90%
“…Although increased T2 times have been observed in mouse gliomas using conventional T2-weighted MRI, this method could not detect gliomas at early stages. 22 Multiexponential T2 has been reported in rat glioblastoma, 23 but the contributing T2 values or underlying factors for multiexponential behavior were not explored. Our method allowed probing at the subvoxel level to quantify pathological T2 with specific information on tumor infiltration.…”
Section: Introductionmentioning
confidence: 99%